2022
DOI: 10.1111/jgh.15973
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different proton pump inhibitors and potassium‐competitive acid blockers on indomethacin‐induced small intestinal injury

Abstract: Author contribution: KML and JNL were involved in the overall design of the experiments. KML, XYC, TTH, and RJ participated in the experiments. KML and JNL wrote the manuscript and assessed and interpreted the results. All authors have read and approved the published version of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A recent animal study reported that P‐CAB aggravated NSAID‐induced SB damage by decreasing the population of Lactobacillus johnsonii in the SB by suppressing gastric acid secretion 6 . Another animal study also showed that vonoprazan, which is a P‐CAB, significantly altered the composition of the intestinal microbiota 29 . However, because PPIs and P‐CABs have different mechanisms of action, it is difficult to determine the effect of P‐CABs on LGI injury in humans through the very few animal studies available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent animal study reported that P‐CAB aggravated NSAID‐induced SB damage by decreasing the population of Lactobacillus johnsonii in the SB by suppressing gastric acid secretion 6 . Another animal study also showed that vonoprazan, which is a P‐CAB, significantly altered the composition of the intestinal microbiota 29 . However, because PPIs and P‐CABs have different mechanisms of action, it is difficult to determine the effect of P‐CABs on LGI injury in humans through the very few animal studies available.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Another animal study also showed that vonoprazan, which is a P‐CAB, significantly altered the composition of the intestinal microbiota. 29 However, because PPIs and P‐CABs have different mechanisms of action, it is difficult to determine the effect of P‐CABs on LGI injury in humans through the very few animal studies available. Further studies on P‐CABs should be conducted to clarify whether the deleterious effects of PPIs on SB damage also apply to P‐CABs.…”
Section: Discussionmentioning
confidence: 99%
“…Rabeprazole treatment regulates ZO-1 expression in the gastric mucosa via the forkhead box F1/signal and the transcription 3 pathway [32] . PPIs may differentially affect the mucosal barrier by altering the composition of the gut microbiota [33] . In this study, inhibition of PAR2 expression protected the esophageal mucosal barrier, and the combination of PAR2 inhibitors and rabeprazole was occasionally superior to the rabeprazole group.…”
Section: Discussionmentioning
confidence: 99%
“…One down-side of blocking acid secretion to treat gastric ulcers was shown, in a small prospective study, to change the duodenal microbiome significantly in favor of pathogenic bacteria [20]. To expand upon this result, studies done in mice pretreated with the ilaprazole, omeprazole, or rabeprazole (PPIs), or vonoprazan (PCAB) showed significant differences in the severity of indomethacin-induced mucosal injury, the rate of mucosal healing, and the disposition of microbiome diversity, community memberships, types of predominant flora, and level of inflammation permitted that was suggested to regulate the profound differences in mucosal pathogenesis [21 ▪▪ ]. For instance, ilaprazole and rabeprazole pretreatment showed nearly opposite changes in the microbiome, which correlated with injury/repair results; ilaprazole pretreatment supported positive changes in the microbiome and blocked mucosal injury and barrier dysfunction whereas rabeprazole pretreatment disrupted the microbiome and resulted in deep lesions that did not heal [21 ▪▪ ].…”
Section: Persistent (Deep) Injury and Mucosal Regenerationmentioning
confidence: 99%
“…To expand upon this result, studies done in mice pretreated with the ilaprazole, omeprazole, or rabeprazole (PPIs), or vonoprazan (PCAB) showed significant differences in the severity of indomethacin-induced mucosal injury, the rate of mucosal healing, and the disposition of microbiome diversity, community memberships, types of predominant flora, and level of inflammation permitted that was suggested to regulate the profound differences in mucosal pathogenesis [21 ▪▪ ]. For instance, ilaprazole and rabeprazole pretreatment showed nearly opposite changes in the microbiome, which correlated with injury/repair results; ilaprazole pretreatment supported positive changes in the microbiome and blocked mucosal injury and barrier dysfunction whereas rabeprazole pretreatment disrupted the microbiome and resulted in deep lesions that did not heal [21 ▪▪ ]. Although studies need to be done in germ-free mice with the same parameters tested in add-back experiments, the results are highly suggestive that drug-induced changes in the microbiome have a profound effect on the severity of mucosal lesions in the gastroduodenal mucosa and their ability to heal.…”
Section: Persistent (Deep) Injury and Mucosal Regenerationmentioning
confidence: 99%